PERBANDINGAN EFEKTIVITAS PEMBERIAN IKAN GABUS DENGAN PUTIH TELUR TERHADAP PENYEMBUHAN LUKA POST SECTION CAESAREA DI RUMAH SAKIT HORAS INSANI TAHUN 2023 - Sagala, Jenny Vivian; Lam Murni Br. Sagala (CV. KAMPUS AKADEMIK PUBLISING, 2025)
Giving birth by surgery or caesarean section is currently a trend for mothers, especially those who are mostly young, but quite a few mothers who give birth by caesarean section experience complications after delivery. However, the needs of post-partum mothers after a cesarean section, one of which is nutrition, also increases, where post-partum mothers require double the nutritional requirements due to the need for breast milk, body recovery and wound healing. If nutritional needs are not met, it can cause the wound to not dry so can cause infection in the wound. The aim of the research was to determine the presentation of snakehead fish and egg whites on wound healing after caesarean section. The research design uses a quasi-experimental, namely post test two group design. The group provided snakehead fish and chicken eggs for 7 days. Wound examination is carried out on the caesarean section wound every 2 days for 7 days. The population in this study was all 97 patients after cesarean section in January - May 2023. Sampling was taken using a purposive sampling technique, that is, every subject who was appropriate and met the inclusion criteria requirements was taken as a sample with a total of 15 respondents in each group. The instruments used were questionnaire sheets and observation sheets with the Man-Whitney hypothesis test because the data was not normally distributed. The conclusion is that there is a comparison of the effectiveness of giving snakehead fish with white eggs in healing wounds after caesarean section at Horas Insani Hospital with a calculated z value of 2.159 > z table 0.4294 and a p value = 0.021 < alpha 0.05. Further suggestions are expected to develop research by providing other non-pharmacological therapies such as early mobilization, giving pineapple juice, quail eggs, binahong leaves and others which can be used to speed up the wound healing process after caesarean section.